Hubungan Perawatan Kaki Dengan Resiko Kajadian Ulkus Kaki Diabetik Pada Penderita Diabetes Melitus Di Wilayah Kerja Puskesmas Sukabumi - Rima Rahmanita; Mustofa Saeful Alamsyah; Egi Mulyadi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Diabetes Mellitus (DM) is a chronic, progressive disease characterized by the body's inability to metabolize carbohydrates, fats and proteins, leading to hyperglycemia (high blood sugar levels). Diabetes Mellitus can be associated with serious complications such as kidney damage, eye problems, cardiovascular disease, nerve damage and skin and foot problems, so DM sufferers need to take precautions to avoid complications. There are several ways to prevent diabetic ulcers, several things that families and patients can do independently, checking the condition of the feet every day for Diabetes Mellitus sufferers needs to be done once a day to detect abnormalities such as redness, blisters, cracked skin, swelling and pain. Objective: To determine the relationship between foot care and the incidence of diabetic foot ulcers in diabetes mellitus sufferers in the Sukabumi Health Center Working Area. Method: The method used in this research is the Descriptive Analytical method with a cross-sectional approach. The samples used were 69 patients suffering from diabetes who were at risk of diabetic foot ulcers in the Sukabumi Community Health Center Working Area. Results: Based on the results of statistical tests with chi-square, the resulting P value was 0.000 < 0.05, which can be concluded that there is a relationship between foot care behavior and the incidence of diabetic ulcers in diabetes mellitus sufferers in the Sukabumi Community Health Center Working Area. Conclusion: it can be concluded that there is a relationship between foot care behavior and the incidence of diabetic ulcers in diabetes mellitus sufferers in the Sukabumi Health Center Work Area. Suggestion: DM sufferers are expected to be disciplined in caring for their feet even though diabetic foot ulcers have not yet occurred and families with diabetes are able to get involved and help if the patient has a serious ulcer, without having to visit health personnel.